Craneotomía vigil como técnica quirúrgica para tratar pacientes que cursan con lesiones cerebrales en áreas del lenguaje - Valenzuela C., Samuel; González V., Rafael; Escobar D., Jaime (Revista Hospital Clínico Universidad de Chile, 2009)
Awake craniotomy is a well established technique, indicated in cases such as neurooncologic surgery among others. The indications of awake craniotomy are classified as anatomical, physiological and pharmacological. Intraparenchimal lesions located adjacent or within eloquent areas are considered to have an anatomical indication. The physiological indication is given in the patients who must undergoe deep brain stimulation. Finally the epileptic patients who must be evaluated by means of intraoperatory electrocorticography are considered to have a pharmacological indication. When patients are carefully selected and well informed about the nature of the procedure, they tolerate adequately this type of surgery, according to our clinical impression and according to the literature. The anesthetic technology has evolved throughout the years, existing nowadays basically two modalities: local anesthesia and sedation and general anesthesia followed by intraoperatory awake (asleep-awake-asleep). In order to practice brain mapping, once the brain is exposed, cortical stimulation is done withstandardized neurophysiological parameters. Language test are carried during stimulation and clinical response is recorded in order to modify the surgical procedure so as to preserve speech. We present a clinical case with an anatomical indication for Awake Craniotomy and where it was possible not just to preserve but also to improve the language in our patient.